New records of Crossodactylus schmidti Gallardo, 1961 (Anura: Hylodidae) for the state of Rio Grande do Sul, Brazil, with data on morphometry and an updated geographic distribution map - Caldart, Vinícius Matheus; Iop, Samanta; de Sá, Fábio Perin [UNESP]; da Rocha, Marcelo Carvalho; de Arruda, Jeferson Luis Steindorff; dos Santos, Tiago Gomes; Cechin, Sonia Zanini (Pensoft Publishers, 2013)
Crossodactylus schmidti Gallardo, 1961 is a diurnal frog inhabiting rocky streams in forested areas, recently considered as a threatened species in the Brazilian states of Rio Grande do Sul and Santa Catarina. Herein we present four new population records of C. schmidti for the northwestern region of Rio Grande do Sul state and discuss the major impacts that may be threatening the species in the state. Additionally, we present an updated map of the current known species distribution and compare morphometric data among populations from Rio Grande do Sul state and Paraná state, in Brazil, and from the province of Misiones, Argentina, based on the examination of voucher specimens available from herpetological collections.© 2013 Check List and Authors.